PENDIDIKAN BERBASIS KELUARGA DALAM KITAB RUT BAGI PELAYANAN S2C DI GBI KELIR SAMARINDA - Novelia Palele; Lina Triana (Sekolah Tinggi Teologi Excelsius, 2018)
Abstract: Theoretical basis: The family is a community that Allah has determined and defined for human needs. Research Objectives: (1) What is meant by family based education? (2) Why are some congregations lazy to follow Serving, and Confidant of God? (3) Why have some Serving, and Confidant of God congregations become discouraged? (4) What is the reason why some congregations refuse to follow Serving, and Confidant of God? (5) How is Family-Based Education and its application for Serving and Confidant of God services at GBI Kelir Samarinda? Method: Qualitative-Observative. Results of the study: (1) This education takes place in the family which is carried out by parents who are given to educate children in the family environment, (2) the congregation thinks the shepherd does not pay attention to it, the shepherd prefers the congregation, the congregation cannot keep secrets, the shepherd cannot be a good example. (3) Not comfortable attending worship, Thinking that this community is not important, Feeling just a waste of time, Worshiping too long. (4) Busy working, no desire to worship, rainy weather conditions, far distance to places of worship, do not have vehicles, do not have offerings for worship, there are conflicts among congregation members that have not been resolved. (5) through the communities of Salvation, Serving, and Confidant of God, we can reach out to every congregation in the church and through the communities of Salvation, Serving, and Confidant of God. Keywords: Education, Family, Service Abstrak: Landasan teori: Keluarga adalah komunitas yang Allah telah tentukan dan tetapkan bagi kebutuhan manusia. Tujuan Penelitian: (1) Apakah yang dimaksud dengan Pendidikan Berbasis Keluarga? (2) Mengapakah beberapa jemaat malas mengikuti Serving, dan Confidant of God? (3) Mengapa beberapa jemaat Serving, dan Confidant of God menjadi tawar hati? (4) Apakah penyebab beberapa jemaat yang tidak mau mengikuti Serving, dan Confidant of God? (5) Bagaimanakah Pendidikan Berbasis Keluarga dan penerapannya bagi pelayanan Serving, dan Confidant of God di GBI Kelir Samarinda? Metode:Kualitatif-Observatif. Hasil Penelitian: (1)Pendidikan ini berlangsung dalam keluarga yang dilaksanakan oleh orang tua yang diberikan untuk mendidik anak dalam lingkungan keluarga, (2) jemaat menilai gembala tidak memerhatikannya, gembala pilih kasih kepada jemaat, jemaat tidak bisa menyimpan rahasia, gembala tidak bisa menjadi teladan yang baik. (3) Kurang nyaman mengikuti ibadah, Menganggap bahwa komunitas ini tidak penting, Merasa hanya membuang waktu saja, Ibadahnya terlalu lama. (4) Sibuk bekerja, Tidak ada kerinduan beribadah, Keadaan cuaca hujan, Jarak tempat beribadah jauh, Tidak mempunyai kendaraan, Tidak mempunyai persembahan untuk beribadah, Ada konflik sesama anggota jemaat yang belum diselesaikan. (5) melalui komunitas Salvation, Serving, dan Confidant of God dapat menjaungkau setiap jemaat-jemaat yang ada di gereja dan melaluin komunitas Salvation, Serving, dan Confidant of God. Kata Kunci: Pendidikan, Keluarga, Pelayanan